2022
DOI: 10.5455/ovj.2022.v12.i6.20
|View full text |Cite
|
Sign up to set email alerts
|

The ability to resist Newcastle disease through inherited immunity in different strains of broilers in Nineveh governorate

Abstract: Background: Newcastle disease (ND) is a viral disease that affects numerous bird species and is still present in many places, including Iraq. Aim: The purpose of this study was to compare maternal derived antibodies (MatAb) against ND vaccination in one-day-old imported Cobb 500 and Ross 308 chicks. Methods: From April to October 2020, four locations in Mosul governorate chosen to compute the maternal derived antibodies (MatAb) from one-day old broiler chicks. Seven hundred and seven blood samples (451) from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…(2021), who reported that MDA persisted for up to 28 days, and Ezzulddin et al. (2022), Kapczynski et al. (2013) and Oberlander et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(2021), who reported that MDA persisted for up to 28 days, and Ezzulddin et al. (2022), Kapczynski et al. (2013) and Oberlander et al.…”
Section: Discussionmentioning
confidence: 96%
“…Cvetic et al (2021), who reported that MDA persisted for up to 28 days, andEzzulddin et al (2022),Kapczynski et al (2013) andOberlander et al (2020), who also observed that MDA persisted up to 27 days of age. Antibodies in chicks endured for 31 days post-birth, inherited from parent stock, with peak titres observed during the layer stage.…”
mentioning
confidence: 94%
“…A decrease in antibodies during heat stress causes an increase in NDV, infectious bursal disease virus (IBDV), and infectious bronchitis disease virus (IBV) (Vandana et al, 2021). According to Ezzulddin et al (2022), antibody values can be influenced by intrinsic and extrinsic factors, including environmental factors, chicken-rearing management factors (vaccine programs), and chicken genetics factors that significantly affect the immune system. In this study, different crude protein levels significantly influence NDV titres.…”
Section: Advances Inmentioning
confidence: 99%